Designing and performance evaluation of metamaterial inspired antenna for 4G and 5G applications. Issue 6 (3rd June 2021) - Singh, Harbinder; Sohi, Balwinder Singh; Gupta, Amit
ABSTRACT: A wideband antenna design with double negative metamaterial (DNG) has been designed and evaluated for 4 G and 5 G applications. The antenna design is investigated for wideband operations for 5 G NR (New Radio) n78 band and TDD LTE (Long Term Evolution) bands from LTE band no. 33 to 43. The design is ruled out for size miniaturisation and wide bandwidth using a radiating-folded dipole. The radiating elements can be tuned to adapt to different configurations using controlling parameters. Moreover, the antenna designed is also investigated for SAR, gain, polarisation and efficiency using metamaterial integration. CST microwave studio is used for designing and analysis of the design and the results are validated for the fabricated prototype. The measured and simulated results are in good agreement with each other and proofs to be a good design for 4 G and 5 G communications.